Diverse and heritable lineage imprinting of early haematopoietic progenitors - Naik, Shalin H.; Perié, Leïla; Swart, Erwin; Gerlach, Carmen; van Rooij, Nienke; de Boer, Rob J.; Schumacher, Ton N. (Nature (London), 2013)
In vivo ‘cellular barcoding’ shows that early haematopoietic progenitors are heterogeneous in the cell types that they produce, and this is partly due to an ‘imprinting’ of fate in progenitors, including for a separate dendritic cell lineage. How multipotent is multipotent? A fundamental question in biology is that of how different tissue types develop from single stem cells. This study tackles the question by following the fate of presumed 'multipotent' lymphoid-primed progenitors (LMPPs) at the single-cell level in mice. Shalin Naik and colleagues used a highly sensitive barcoding method to track the lineage output of hundreds of single LMPPs and haematopoietic stem cells in vivo . They find that not all presumed 'multipotent' progenitors are especially 'multi-outcome': rather, many LMPPs produce a single lineage of cells. The authors also found an unexpectedly large number of LMPPs with a unique dendritic cell potential, which suggests that the dendritic cell lineage is distinct from the myeloid and B-cell branches. Haematopoietic stem cells (HSCs) and their subsequent progenitors produce blood cells, but the precise nature and kinetics of this production is a contentious issue. In one model, lymphoid and myeloid production branch after the lymphoid-primed multipotent progenitor (LMPP) 1 , with both branches subsequently producing dendritic cells 2 . However, this model is based mainly on in vitro clonal assays and population-based tracking in vivo , which could miss in vivo single-cell complexity 3 , 4 , 5 , 6 , 7 . Here we avoid these issues by using a new quantitative version of ‘cellular barcoding’ 8 , 9 , 10 to trace the in vivo fate of hundreds of LMPPs and HSCs at the single-cell level. These data demonstrate that LMPPs are highly heterogeneous in the cell types that they produce, separating into combinations of lymphoid-, myeloid- and dendritic-cell-biased producers. Conversely, although we observe a known lineage bias of some HSCs 11 , 12 , 13 , 14 , most cellular output is derived from a small number of HSCs that each generates all cell types. Crucially, in vivo analysis of the output of sibling cells derived from single LMPPs shows that they often share a similar fate, suggesting that the fate of these progenitors was imprinted. Furthermore, as this imprinting is also observed for dendritic-cell-biased LMPPs, dendritic cells may be considered a distinct lineage on the basis of separate ancestry. These data suggest a ‘graded commitment’ model of haematopoiesis, in which heritable and diverse lineage imprinting occurs earlier than previously thought.